Consumer-SLAPP: The Concept of Legal Protection for Influencers as Consumers in Digital Review - Farel Putra Betharyana; Gusti Yosi Andri (Jurnal Legisci, 2026)
Background. The development of digital space has created legal uncertainty regarding the position of influencers who deliver reviews of goods and/or services based on their personal experience as consumers. Aims. This research aims to analyze the legal standing of influencers as consumers in digital review activities and to examine the application of H.L.A. Hart's The Concept of Law to the legal protection of such activities. Methods. This research employs a normative juridical method using statutory and conceptual approaches. Legal materials, comprising primary, secondary, and tertiary sources, were analyzed qualitatively through grammatical, systematic, and conceptual interpretation. Result. The results show that influencers may have the legal standing of consumers insofar as they use goods and/or services for personal purposes rather than for resale. This standing entitles influencers to express opinions, assessments, and complaints regarding the products used, including through digital reviews. However, the development of digital space has led to reviews being perceived as public information that can affect business reputation, prompting the use of legal instruments against consumer reviews. Based on Hart's theory, this condition reflects uncertainty in primary rules due to the absence of specific regulations protecting consumer review activities in the digital space. Conclusion. The concept of Consumer-SLAPP is proposed as a legal protection framework to recognize influencers' standing as consumers and safeguard honest, objective, and good-faith reviews. Implication. This research implies the need for regulatory reform in consumer protection law to address the evolving dynamics of digital consumer participation.